Determination of Employee Resign Decision: Corporate Culture and Career Development - Djoko Setyo Widodo (Journal of Accounting and Finance Management, 2021)
This study aims to determine the factors that influence company resignation decisions, which include company culture and career development. The object of this study is previous research that is relevant to this research. The method used in this study is descriptive qualitative, sourced from previous research that is useful for further research. The results of this study are: 1) Company culture influences employee resignation decisions; 2) Career development affects employee resignation decisions; and 3) Corporate culture affects career development.